NcROP2 deletion reduces Neospora caninum virulence by altering parasite stage differentiation and hijacking host immune response - Amieva, Rafael; Coronado, Montserrat; Powell, Jessica; Arranz-Solís, David; Hassan, Musa A.; Collantes-Fernández, Esther; Ortega-Mora, Luis Miguel; Horcajo, Pilar (Frontiers in Immunology, 2025)
IntroductionNeospora caninum is an apicomplexan parasite responsible for bovine neosporosis, a major cause of abortion in cattle worldwide. N. caninum rhoptry protein 2 (NcROP2) has been identified as an essential factor in host cell invasion and parasitophorous vacuole formation, making it a potential target for disease control strategies.MethodsIn this study, we generated NcRop2 knockout (NcΔROP2) mutants using CRISPR/Cas9 technology to assess their role in parasite virulence.ResultsIn a pregnant mouse model, NcΔROP2 parasites exhibited reduced virulence, as indicated by increased neonatal survival rates and lower parasite burden in the brain and attenuated clinical signs in the dams compared to the wild-type (Nc-Spain7) parental strain. Additionally, the NcΔROP2 mutants exhibited impaired proliferation and significantly induced the expression of interferon-stimulated genes in bovine monocyte-derived macrophages infected in vitro for 60 hours. Transcriptomic analysis further revealed a shift in parasite gene expression, with an upregulation of stress-related and bradyzoite markers. Functional assays confirmed that NcΔROP2 parasites were less susceptible to IFN-γ-mediated inhibition and displayed an enhanced ability to convert to the semi-dormant bradyzoite stage.DiscussionThese findings highlight NcROP2 as a key virulence factor involved in immune evasion and parasite proliferation, providing new insights into N. caninum infection pathogenesis and potential avenues for vaccine development.